Synthesis and Anti-inflammatory Activity of Some Novel 3-(6-Substituted-1, 3-benzothiazole-2-yl)-2-[{(4-substituted phenyl) amino} methyl] quinazolines-4 (3H)-ones - Manish Srivastav; MD. Salahuddin; S. M. Shantakumar (E-Journal of Chemistry)
A series of novel 3-(6-substituted-1, 3-benzothiazole-2-yl)-2-[{(4-substituted phenyl) amino} methyl] quinazolines-4(3H)-ones were synthesized by treating 2-(chloromethyl)-3-(6-substituted-1, 3-benzothiazole-2-yl) quinazoline-4-(3H)-one (IIa-d) with various substituted amine. The compounds (IIa-d) prepared by treating 2-[(chloroacetyl) amino] benzoic acid with different 2-amino-6-substituted benzothiazole. Elemental analysis, IR, 1HNMR and mass spectral data confirmed the structure of the newly synthesized compounds. Synthesized quinazolines-4-one derivative were investigated for their anti-inflammatory and antibacterial activity.